Exploring Role of Technology Performance Expectancy, Application Effort Expectancy, Perceived Risk and Perceived Cost On Digital Behavioral Intention of GoFood Users - Tannady, Hendy; Dewi, Cynthia Sari; Gilbert (Jurnal Informasi dan Teknologi, 2024)
In the current era of globalization, organizational culture cannot be separated from Human Resources, which is one of the main elements that occupies an important and strategic position in improving company quality. By using these Human Resources in the current era of globalization and increasingly sophisticated technology, it makes it easier for people to access any activity via technology. The online delivery service feature is useful for buying food that consumers want without having to waste time queuing and traveling. In fact, consumers often experience problems when ordering food via online delivery orders. However, providers of online delivery features are still able to convince consumers to stay and continue to use these features. In this research the author used a quantitative approach. The quantitative approach is the measurement of objective quantitative and statistical data through scientific calculations derived from samples of people or residents who are asked to answer a number of questions on a survey to determine the frequency and percentage of their responses. In this quantitative theory, research will be predetermined, analyzing statistical data and interpreting statistical data.The population in this study was 100 random online or remote application users of the GoFood application. The research method used is the explanatory survey research method. Data collection used is a questionnaire or self-administered questionnaire. The research results prove that using this online application can make it easier and create a culture among people to order online. Of course, the nature of new culture or traditions can influence people's behavior in carrying out transactions every day, especially in terms of food products that every Indonesian citizen needs every day.